2022
DOI: 10.21203/rs.3.rs-1555201/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety, Immunogenicity and Antibody Persistence of a Bivalent Beta-Containing Booster Vaccine

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) variants have caused multiple waves of infection globally. This phase 2/3 study evaluated the safety and immunogenicity of the bivalent vaccine candidate mRNA-1273.211 (equal mRNA amounts of ancestral SARS-CoV-2 and Beta variant spike proteins) as 50-µg (n=300) and 100-µg (n=595) first booster doses approximately 8.8-9.8 months after the mRNA-1273 primary series. The mRNA-1273.211 booster (50 and 100-µg) elicited higher neutralizing antibody response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 0 publications
5
30
0
Order By: Relevance
“…We had previously reported that a bivalent booster vaccine containing the ancestral SARS-CoV-2 and an antigenically-divergent variant can induce antibodies which cross-neutralize and cross-react with multiple variants and consistently elicit higher antibody responses compared to mRNA-1273. 23 mRNA-1273.214 elicited potent neutralizing antibodies responses against the omicron BA.4 and BA.5 subvariants and the increase (fold-rise) in neutralizing antibody titers was consistent with the increase in titers against omicron BA.1, regardless of prior SARS-CoV-2 infection. In addition, the longevity of the neutralizing antibody response is important and we previously observed a more durable response against multiple variants, 6 months after immunization with the beta-containing bivalent vaccine, compared to mRNA-1273.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…We had previously reported that a bivalent booster vaccine containing the ancestral SARS-CoV-2 and an antigenically-divergent variant can induce antibodies which cross-neutralize and cross-react with multiple variants and consistently elicit higher antibody responses compared to mRNA-1273. 23 mRNA-1273.214 elicited potent neutralizing antibodies responses against the omicron BA.4 and BA.5 subvariants and the increase (fold-rise) in neutralizing antibody titers was consistent with the increase in titers against omicron BA.1, regardless of prior SARS-CoV-2 infection. In addition, the longevity of the neutralizing antibody response is important and we previously observed a more durable response against multiple variants, 6 months after immunization with the beta-containing bivalent vaccine, compared to mRNA-1273.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, the longevity of the neutralizing antibody response is important and we previously observed a more durable response against multiple variants, 6 months after immunization with the beta-containing bivalent vaccine, compared to mRNA-1273. 23 We will continue to monitor the persistence of the antibody responses elicited by mRNA-1273.214 in the ongoing clinical study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a booster dose of the mRNA-1273 vaccine resulted in neutralisation titres against Omicron that were 20-times higher than one month after the second dose of vaccine ( 118 ). Boosting with a bivalent ancestral and Beta (mRNA-1273.211) or Beta and Delta (mRNA-1273.213) vaccine resulted in almost identical neutralisation titres for Omicron as individuals who received a booster with mRNA-1273 alone ( 118 ) ( 137 ). Interestingly, in a recent study that investigated protective immune responses against Omicron in macaques immunized with mRNA-1273 or an mRNA-Omicron vaccine ( 138 ), there was no increased response to Omicron in animals boosted with the Omicron vaccine.…”
Section: Immune Imprinting: a Partnership Of Infection And Vaccine In...mentioning
confidence: 99%
“…Bivalent vaccines have become effective tools to respond to the emerging variants. The bivalent vaccine mRNA-1273.211 targeting the prototype and beta strain induced more potent, durable, and wilder humoral responses against key previously circulating VOCs and VOIs, which is superior to mRNA-1273 regarding titers against some VOIs, but also equivalent to peak titers measured after the primary vaccine series against prototype strain [ 25 , 26 ]. Based on the same strategy, the bivalent vaccine mRNA-1273.214 targeting the prototype and Omicron strain has elicited superior neutralizing antibody response against Omicron and non-inferior response against prototype SARS-CoV-2 compared with mRNA-1273 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%